Optimum Planting Time of Lentil (Lens culinaris) in Rice-Fallow Lands in Tripura - Yadav, Gulab Singh; Kandpal, Basant; Barman, K.K. (Indian Journal of Hill Farming, 2019)
A field experiment was conducted during 2013-14 and 2014-15 to identify an optimum sowing time of lentil under rice-fallow condition of Tripura. The experiment consisting of six dates of lentil sowing, i.e. Oct 25, Nov 5, Nov 15, Nov 25, Dec 5 and Dec 15, was laid out in a randomized complete block design with three replications. The study revealed that the lentil sown between Nov 5 to Nov 25 had significantly higher plant height, primary and secondary branches, the number of nodule and nodule dry weight per plant and root length in comparison to the crops planted on Oct 25, Dec 5, and Dec 15. Among the lentil sowing dates tested, the Nov 15 sowing resulted in significantly highest number of pods per plant and seed yield (1020 kg/ha), and it was statistically similar to Nov 5 and Nov 25. It was concluded that lentil is a potential candidate for crop diversification and could be sown from Nov 5 to Nov 25 in the low land rice-fallow conditions of Tripura for augmenting the farmers’ income.